2018
DOI: 10.1155/2018/4929805
|View full text |Cite
|
Sign up to set email alerts
|

Direct Microscopy of Stool Samples for Determining the Prevalence of Soil-Transmitted Helminthic Infections among Primary School Children in Kaduwela MOH Area of Sri Lanka following Floods in 2016

Abstract: A descriptive cross-sectional school based study was carried out to investigate the prevalence of soil-transmitted intestinal helminths and the associated factors among school children in Kaduwela Medical Officer of Health (MOH) area in the Colombo district, which was affected by floods in 2016. The study was conducted in 9 selected schools in Kaduwela MOH area from September 2016 to March 2017. Permission was obtained from the relevant authorities. Grade 1 students were enrolled in the study after obtaining i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Being advised to check stool samples to diagnose parasitic infections may be related to accurate knowledge overall, which should result in further improvements in practice. In line with the findings presented here, a survey in Sri Lanka found that individuals who had been advised on how to prevent STH infections demonstrated improved health practices [30]. VHVs with good knowledge were more likely to have good practices.…”
Section: Discussionsupporting
confidence: 88%
“…Being advised to check stool samples to diagnose parasitic infections may be related to accurate knowledge overall, which should result in further improvements in practice. In line with the findings presented here, a survey in Sri Lanka found that individuals who had been advised on how to prevent STH infections demonstrated improved health practices [30]. VHVs with good knowledge were more likely to have good practices.…”
Section: Discussionsupporting
confidence: 88%
“…In 2016, a survey of children attending 9 schools in the Kaduwela area which had been severely affected by floods, found that none of the 156 faecal samples examined by normal saline smears were positive for STH eggs. 15 A detailed study conducted in the estate sector, which remains a high-risk community for STH infections in Sri Lanka, has examined in depth, factors that affect the prevalence of STH infections, to facilitate greater effectiveness in control activities. Different aspects of this study have been presented in sequential papers.…”
Section: Prevalence Of Sth Infections and Factors Affecting Transmissionmentioning
confidence: 99%